2009
DOI: 10.1097/bot.0b013e31819b24e9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Clinical and Radiologic Outcomes of Unstable Colles Type Distal Radius Fractures in Patients Older Than 70 Years: Nonoperative Treatment Versus Volar Locking Plating

Abstract: Radiographic results (dorsal tilt, radial inclination, and radial shortening) after unstable dorsally displaced DRFs are significantly better in patients treated by ORIF using a volar fixed-angle plate rather than those treated by cast immobilization (P < 0.05). At a mean follow-up time of 4 years and 7 months, the clinical outcomes of active range of motion, the PRWE, DASH, and Green and O'Brien scores do not differ between the 2 methods of treatment. The pain level was significantly less in the CAST group (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
215
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(241 citation statements)
references
References 28 publications
(35 reference statements)
12
215
1
13
Order By: Relevance
“…Do these patients require more pain medications, more recovery room time, and/or have functional outcomes or patient satisfaction differences? In addition, we currently have little understanding regarding how to advise patients about optimal pain control after distal radius fracture fixation [1,2,9,12]. We therefore decided to conduct a randomized study comparing pain control after distal radius fracture fixation in patients who received either general anesthesia or brachial plexus blockade to better understand this.…”
Section: Introductionmentioning
confidence: 99%
“…Do these patients require more pain medications, more recovery room time, and/or have functional outcomes or patient satisfaction differences? In addition, we currently have little understanding regarding how to advise patients about optimal pain control after distal radius fracture fixation [1,2,9,12]. We therefore decided to conduct a randomized study comparing pain control after distal radius fracture fixation in patients who received either general anesthesia or brachial plexus blockade to better understand this.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of distal radius fractures increase in two distinct age groups in which the injury occurs by two distinct mechanisms: high energy falls during sports activities in young and low energy falls in elderly patients with various risk factors. Closed reduction and cast stabilization is the accepted treatment in most cases, especially in lowdemand elderly patients [2][3][4], whereas operative treatment provides better anatomical stabilization of the wrist and earlier improvement of functions in patients who had professional expectations.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 The results of this retrospective study are comparable with those reported by various authors in terms of early functional recovery and acceptable radiological parameters. 3,6,11 The modified Green and O'Brien Score showed 5(21 Percent) excellent, 13(54 Percent) good, 5(21 Percent) fair, and 1(4 Percent) poor results at the latest follow-up. Arora, et al 3 reported 31(27%) excellent, 54(47%) good, 23(20%) fair, and 6(5%) poor results in their multicenter study.…”
Section: Modified Clinical-scoring System Of Green and O'brienmentioning
confidence: 99%
“…Although cast treatment gives good functional outcome in geriatric patients, 2,3 it has given way to operative methods for better outcome in high-demand younger patients. A multiple array of surgical techniques for fixation of distal radius fracture are available which include pins and plaster, spanning external fixator, percutaneous pinning and various types of plates and screws.…”
Section: Introductionmentioning
confidence: 99%